Lived experiences of food-related emotional expectancies across socioeconomic groups in adults with overweight/obesity: A co-produced mixed-methods study - Maddy Roberts; Isabelle Ince; Beccie Neubeck; Sarah-Kate O'Hara; Tracy Hammond; Simon Collyer; Helen West; Anna Chisholm; Eric Robinson; Jenna R. Cummings (Appetite, 2026)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Performance evaluation and microbial dynamics of submerged anaerobic membrane bioreactors for municipal wastewater treatment - F. Yilmaz; E.G. Özbayram; N.A. Perendeci; E. Sahinkaya; O. İnce (Journal of Water Process Engineering, 2024)

Poor perfusion of the microvasculature in peritoneal metastases of ovarian cancer - Arnoud W. Kastelein; Laura M. C. Vos; Juliette O. A. M. van Baal; Jasper J. Koning; Vashendriya V. V. Hira; Rienk Nieuwland; Willemien J. van Driel; Zühre Uz; Thomas M. van Gulik; Jacco van Rheenen; Can Ince; Jan-Paul W. R. Roovers; et al. (Clinical & Experimental Metastasis, 2020)
Most women with epithelial ovarian cancer (EOC) suffer from peritoneal carcinomatosis upon first clinical presentation. Extensive peritoneal carcinomatosis has a poor prognosis and its pathophysiology is not well understood. Although treatment with systemic intravenous chemotherapy is often initially successful, peritoneal recurrences occur regularly. We hypothesized that insufficient or poorly-perfused microvasculature may impair the therapeutic efficacy of systemic intravenous chemotherapy but may also limit expansive and invasive growth characteristic of peritoneal EOC metastases. In 23 patients with advanced EOC or suspicion thereof, we determined the angioarchitecture and perfusion of the microvasculature in peritoneum and in peritoneal metastases using incident dark field (IDF) imaging. Additionally, we performed immunohistochemical analysis and 3-dimensional (3D) whole tumor imaging using light sheet fluorescence microscopy of IDF-imaged tissue sites. In all metastases, microvasculature was present but the angioarchitecture was chaotic and the vessel density and perfusion of vessels was significantly lower than in unaffected peritoneum. Immunohistochemical analysis showed expression of vascular endothelial growth factor and hypoxia inducible factor 1α, and 3D imaging demonstrated vascular continuity between metastases and the vascular network of the peritoneum beneath the elastic lamina of the peritoneum. We conclude that perfusion of the microvasculature within metastases is limited, which may cause hypoxia, affect the behavior of EOC metastases on the peritoneum and limit the response of EOC metastases to systemic treatment.

Monitoring the abundance and the activity of ammonia-oxidizing bacteria in a full-scale nitrifying activated sludge reactor - Ö. Eyice; O. Ince; B. K. Ince (Environmental Science and Pollution Research, 2015)

Effect of seed sludge microbial community and activity on the performance of anaerobic reactors during the start-up period - N. A. Oz; O. Ince; G. Turker; B. K. Ince (World Journal of Microbiology and Biotechnology, 2012)

Restoration of the eutrophic Lake Eymir, Turkey, by biomanipulation after a major external nutrient control I - M. Beklioglu; O. Ince; I. Tuzun (Hydrobiologia, 2003)